Analisis Daya Tahan Kardiorespirasi melalui Tes Lari 1000 Meter pada Siswa Kelas IV SDN Percobaan 1 Malang sebagai Dasar Evaluasi Pembelajaran PJOK bagi Mahasiswa PPG - Alief Maulafajrin, Achmad; Alfan, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cardiorespiratory endurance is one of the important components of physical fitness that supports students' ability to participate in Physical Education, Sports, and Health (PJOK) learning. This study aims to analyze the cardiorespiratory endurance of grade IV students of SDN Experimental 1 Malang through a 1000-meter running test as the basis for evaluating PJOK learning for Teacher Professional Education (PPG) students. The research uses a quantitative approach with a descriptive method. The research subjects amounted to 28 grade IV students who were selected using the total sampling technique. Data collection was carried out through a 1000-meter running test to measure students' cardiorespiratory endurance ability. The data were analyzed using descriptive statistics which included mean values, minimum values, maximum values, and standard deviations. The results of the study showed that the average travel time for students in completing the 1000-meter running test was 7.79 minutes, with the fastest time of 5.42 minutes and the longest time of 11.45 minutes. The standard deviation value of 1.47 indicates a variation in cardiorespiratory endurance ability between students. The results indicate that the level of cardiorespiratory endurance of students still needs to be improved. The findings of this research can be used as the basis for evaluating PJOK learning for PPG students in designing learning activities that are in accordance with the physical conditions, characteristics, and needs of students so that they can support the improvement of students' physical fitness more effectively.